2011
DOI: 10.2478/v10019-011-0013-8
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of stat3 expression by RNAi inhibits in vitro growth of human ovarian cancer

Abstract: BackgroundThe aim of the study was to investigate the suppressive effects of pSilencer2.1-U6-siRNA-stat3 recombinant plasmids on the growth of ovarian cancer in vitro.Material and methods.Three pairs of DNA template (stat3-1, stat3-2, stat3-3) specific for different target sites on stat3 mRNA were synthesized to reconstruct pSilencer2.1-U6-siRNA-stat3s, which were transfected into SKOV3 cells. The expressions of STAT3, BcL-2, cyclin D1 and C-myc in these cells were detected by Western blot and Northern blot. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 27 publications
(32 reference statements)
0
12
0
Order By: Relevance
“…It was reported that the suppression of Cyclin D1 with antisense induces both cell growth arrest and apoptosis [44,45]. Also, it was shown that the knockdown of STAT3 expression by RNA interference (RNAi) suppresses the growth of SKOV3 cells and arrests the cell cycle in the G1 phase [46]. Consistent with our findings, the authors mentioned that “cells transfected with siRNA-stat3 became less confluent and some cells were rounded and detached from the plates, when compared with cells transfected with scrambled vectors”.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that the suppression of Cyclin D1 with antisense induces both cell growth arrest and apoptosis [44,45]. Also, it was shown that the knockdown of STAT3 expression by RNA interference (RNAi) suppresses the growth of SKOV3 cells and arrests the cell cycle in the G1 phase [46]. Consistent with our findings, the authors mentioned that “cells transfected with siRNA-stat3 became less confluent and some cells were rounded and detached from the plates, when compared with cells transfected with scrambled vectors”.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of STAT3 with the orally active JAK inhibitor, AZD1480, was found to decrease tumor growth in neuroblastoma and pediatric sarcomas through downregulation of cell cycle regulators, cyclin D1, cyclin D3 and cdc25A, anti-apoptotic genes Bcl-2 and survivin, the metastasis-related factor TIMP-1, and c-Myc. Knockdown of STAT3 expression by RNAi inhibited the growth of human ovarian cancer through downregulation of cyclin D1, c-Myc and Bcl-2 [145].…”
Section: Proliferationmentioning
confidence: 99%
“…Persistent activation of STAT3 has been reported in ovarian cancer cells [23]. Research using RNAi technology to knockdown the STAT3 gene in ovarian cancer cells has also been reported [24,25].…”
Section: Introductionmentioning
confidence: 99%